2020
DOI: 10.1111/ggi.14002
|View full text |Cite
|
Sign up to set email alerts
|

Association between heart diseases, social factors and physical frailty in community‐dwelling older populations: The septuagenarians, octogenarians, nonagenarians investigation with centenarians study

Abstract: Heart diseases and social factors are associated with physical frailty, but there are few studies of older people living in the community. Consequently, the aim of this study was to examine the association between heart diseases, social factors and physical frailty in community-dwelling older populations including the oldest-old people. Methods: The cross-sectional study included 1882 participants of community-dwelling older and oldest-old people. The survey site assessed questionnaires on medical history, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
0
9
0
3
Order By: Relevance
“…A literature review revealed that sociodemographic factors (such as sex, age, education level, and income) [ 13 ], physiological factors (such as genes, inflammatory factors, body composition, and malnutrition) [ 14 17 ], chronic diseases (such as diabetes, cardiovascular disease, and stroke) [ 18 ], lifestyles (such as physical activity, sedentary lifestyle, fruit and vegetable consumption, and dietary patterns) [ 19 21 ] and psychological factors (such as stress, depression, and anxiety) [ 22 24 ] may cause frailty. In addition, studies have also found that social factors such as social isolation [ 25 ], frequency of interaction with relatives and friends [ 26 ], and social support [ 27 ] were associated with frailty. However, the social factors in these studies were predominantly examined at individual level, and few studies investigated the association between overall social factors, such as social capital, and frailty [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…A literature review revealed that sociodemographic factors (such as sex, age, education level, and income) [ 13 ], physiological factors (such as genes, inflammatory factors, body composition, and malnutrition) [ 14 17 ], chronic diseases (such as diabetes, cardiovascular disease, and stroke) [ 18 ], lifestyles (such as physical activity, sedentary lifestyle, fruit and vegetable consumption, and dietary patterns) [ 19 21 ] and psychological factors (such as stress, depression, and anxiety) [ 22 24 ] may cause frailty. In addition, studies have also found that social factors such as social isolation [ 25 ], frequency of interaction with relatives and friends [ 26 ], and social support [ 27 ] were associated with frailty. However, the social factors in these studies were predominantly examined at individual level, and few studies investigated the association between overall social factors, such as social capital, and frailty [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority ( n = 129, 70.5%) of the included studies' populations were older adults with no defined conditions. The remaining 54 articles (29.5%) included older adults with dementia or cognitive impairment, 34–59 fragile X syndrome associated with tremor/ataxia, a condition resulting from a gene permutation, 60 stroke, 61,62 chronic obstructive pulmonary disease, 63 cancer, 64,65 diabetes, 66 Parkinson's disease, 17,67–74 cardiovascular disease, 14,75–80 lower back pain, 81 multiple comorbidities 82–84 and post‐menopausal conditions 85 . Most studies recruited participants from the community ( n = 164, 89.6%), and the remaining studies ( n = 19, 10.4%) recruited from the hospital and long‐term care setting or both the long‐term care and community setting, or did not report the setting from which the participants were recruited.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported that increased social activity, 186 increased social interaction, 77 and increased social integration and availability of emotional and tangible social support 187 were associated with better walking outcomes in older adults. Better social well‐being 179 and increased social engagement 45 were associated with better physical functioning in older adults.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, pre-frail participants represented almost half of the study sample and, according to the scientific literature, this condition has a greater chance of improving than frailty 26 . In addition, the characteristics of the pre-frail participants, such as living alone 9,12 and the presence of morbidity 13 , may also negatively impact the components of the frailty phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of frailty syndrome is significantly greater in the oldest old, with rates of 11.2-84.7% [5][6][7] reported in the international literature and 14.8-58.0% [8][9][10] in national studies. However, investigations in oldest old reveal that, besides more advanced age 6,9 , frailty syndrome is associated with being female 6,11 ; having no partner 12 ; high number of morbidities 13 ; presence of depressive symptoms 5,14,15 , poor physical performance 5,16 and with functional disability for performing activities of daily living (ADLs) 7,15 .…”
Section: Introductionmentioning
confidence: 99%